PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN POLITEKNIK MANUFAKTUR BANDUNG - Desfitriady; Muhammad Nurfairy (JURNAL BISNIS dan TEKNOLOGI, 2023)
his study aims to determine compensation and work discipline on employee performance, and to determine how much influence compensation and work discipline have on employee performance both partially and simultaneously on employees of the Bandung Manufacturing Polytechnic (POLMAN) with civil servant status. The type of research used in this research is descriptive and associative. The number of samples used in this study were 136 respondents taken from employees with employment status as civil servants. To see the effect between the 2 variables, this analysis uses multiple linear regression analysis method. This study resulted that the effect of compensation on employee performance partially by 10.6%. The effect of work discipline on employee performance is partially 61.3%, so that compensation and work discipline on employee performance simultaneously are 71.9%, while the rest are influenced by variables that are not examined.